Using ultrasound and palpation for predicting axillary lymph node status following neoadjuvant chemotherapy – Results from the multi-center SENTINA trial. (February 2017) - Schwentner, Lukas; Helms, Gisela; Nekljudova, Valentina; Ataseven, Beyhan; Bauerfeind, Ingo; Ditsch, Nina; Fehm, Tanja; Fleige, Barbara; Hauschild, Maik; Heil, J.; Kümmel, Sherko; Lebeau, Anette; et al.
Abstract: Background: With the growing importance of neoadjuvant systemic therapy (NST) the assessment of post neoadjuvant axillary status is of increasing importance especially in patients who presented initially with suspicious nodes (cN1). This study aims to investigate the predictive value of palpation and axillary ultrasound of formerly cN1 patients following NST. Patients and methods: The SENTINA trial (SENTinel NeoAdjuvant) is a 4-arm prospective multicenter study designed to evaluate the role of sentinel node biopsy (SLNB) in the context of neoadjuvant systemic treatment (NST) of breast cancer patients. Results: 1240 patients from 103 institutions entered the trial. 715 (arm C n = 592; arm D n = 123) patients, who presented initially cN1 underwent clinical evaluation of lymph node status following NST. Palpation alone demonstrated a sensitivity of 8.3%, specifity of 94.8% and a negative predictive value (NPV) of 46.6%. Ultrasound alone revealed a sensitivity of 23.9%, specificity 91.7%, and a NPV of 50.3%.The investigators combined classification (palpation and ultrasound) resulted in a sensitivity of 24.4%, specificity 91.4%, and a NPV of 50.3%. Investigators classified the axilla nodes as being unsuspicious (cN0) following NST in 592/715 patients; of them 298 (50.3%) were pN0, 151 (25.5%) had 1-2 histologically involved nodes and 143 (24.2%) had >2 histologically involved nodes. Conclusion: The diagnostic accuracy of ultrasound and palpation following NST is unacceptably low and additional tools for evaluation of the axillary lymph node status following NST are urgently needed. Highlights: Diagnostic accuracy of palpation and ultrasound is negatively influenced by Prior neoadjuvant chemotherapy. False negative rates are inacceptabely high especially in the ycN0 subset. Improving the accuracy in predicting axillary lymph node Status will need comprehensive models or clipping procedures.